Neonatal risk factors associated with attention-deficit/hyperactivity disorder: an umbrella review - Ensiyeh Jenabi; Erfan Ayubi; Sajjad Farashi; Saeid Bashirian; Fereshteh Mehri (The Korean Pediatric Society, 2023)
Background Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder that is being encountered more frequently. Purpose In this study, by compiling the evidence from available meta-analyses, an umbrella systematic review was performed of the neonatal risk factors associated with ADHD. Methods The PubMed, Scopus, and Web of Science databases were searched for eligible studies. Only systematic reviews were included. Using a random-effects model, 95% prediction intervals were reported for each risk factor. Three studies were ultimately included in the review. Results Congenital heart disease, short-duration or incomplete breastfeeding, low birth weight, and 5-minute Apgar scores <7 were significant risk factors for ADHD. However, the quality of the included systematic reviews was low to moderate and the evidence credibility level was suggestive to weak. Conclusion The results of this umbrella review proposed that congenital anomalies, short-duration or incomplete breastfeeding, low birth weight, and low Apgar scores were important factors for the manifestation of ADHD symptoms. However, the inclusion of more high-quality studies is needed to validate our results.